![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(xy+2x+y+11=0\)
\(\Leftrightarrow x\left(y+2\right)+\left(y+2\right)+9=0\)
\(\Leftrightarrow\left(x+1\right)\left(y+2\right)=0-9\)
\(\Leftrightarrow\left(x+1\right)\left(y+2\right)=-9\)\(=-1.9=-3.3=-9.1\)
\(\Rightarrow\left[{}\begin{matrix}x+1=-1;y+2=9\\x+1=-3;y+2=3\\x+1=-9;y+2=1\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-2;y=7\\x=-4;y=1\\x=-10;y=-1\end{matrix}\right.\)
Vậy:.............
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1 : a) 3x2 +21x=0
3x(x+7)=0
=> x=0 hoặc x+7=0 =>x=0 hoặc x= -7
b)5x-6x2=0
x(5-6x)=0
=> x=0 hoặc 5-6x=0 => x=0 hoặc x=\(\frac{5}{6}\)
\(3x^2+21x=0\)
\(\Rightarrow3x\left(x+7\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x=0\\x+7=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=-7\end{cases}}\)
\(5x-6x^2=0\)
\(\Rightarrow x\left(5-6x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\5-6x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{5}{6}\end{cases}}}\)
\(\left(2x+3\right)\left(y-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x+3=0\\y-5=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{3}{2}\\x=5\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
xy+x+y+1=0
x(y+1)+(y+1)=0
(x+1)(y+1)=0
\(\Leftrightarrow\)x+1=0→x=-1
và y+1=0→y=-1
![](https://rs.olm.vn/images/avt/0.png?1311)
a)(x-1)(y+2)=7
=>x-1=1;y+2=7 hoặc x-1=7 ; y+2=1 hoặc x-1=-1;y+2=-7
=>x=2;y=5 hoặc x=8;y=-1hoặc x=0 hoặc y=-9
b)x(y-3)=-12
=>x=-3;y-3=4 hoặc x=3 ; y-3=-4 hoặc x=1 ;y-3=-12 hoặc x=-1 ;y-3=12
=>x=-3;y=7 hoặc x=3 ;y=-1 hoặc x=1 ;y=-9 hoặc x=-1;y=15
\(xy-2x+y+1=0\\ xy-2x+y+1-3=0-3\\ x\cdot\left(y-2\right)+\left(y-2\right)=-3\\ \left(x+1\right)\left(y-2\right)=-3=\left(-1\right)\cdot3=1\cdot\left(-3\right)\\ \left\{{}\begin{matrix}x+1=-1=>x=-2\\y-2=3=>y=5\end{matrix}\right.\\ \left\{{}\begin{matrix}x+1=1=>x=0\\y-2=-3=>y=-1\end{matrix}\right.\)
vậy (x; y) ∈ {(-2; 5); (0; -1)}
xy-2x+y+1=0
Xy-2x+y=-1
X(y-2)+y=-1
X(y-2)+(y-2)=-1
(x+1)(y-2)=1
Suy ra x+1\(\in\) Ư(1)={-1;1}
x+1
-1
1
x
-2
0
y-2
-1
1
y
1
3